CONSTRUCTION OF A DIFLUNISAL ION SENSOR AND ITS USE IN AUTOMATED FLOW-INJECTION METHODS FOR ASSAY, CONTENT UNIFORMITY, AND DISSOLUTION STUDIES OF FORMULATIONS - SOLICH, P; Macheras, PE; Koupparis, MA (JOURNAL OF PHARMACEUTICAL SCIENCES, 1995)
A diflunisal ion selective electrode of the PVC membrane type with an ion-exchanger consisting of the tetraheptylammonium-diflunisal ion pair is described. The sensor exhibits a rapid, near-Nernstian, selective response to diflunisal anion in the pH range 7-10, with a (batch) detection limit of 1 x 10(-5) M. The ion sensor was used as a flow detector in an automated flow-injection analyzer to develop routine methods for assays (concentration range 1-50 x 10(-4) M, (flow) detection limit 2.6 x 10(-5) M), content uniformity, and dissolution studies of diflunisal formulations. No serious interference from common ions and tablet excipients was found, and the drug can be directly determined in colored samples without separation steps. Fourty measurements can be performed automatically per hour with a precision of 0.5-1.8% relative standard deviation. The automated method for the dissolution test provides a complete dissolution profile by the end of the experiment. Using the constructed ion sensor, the intramolecular hydrogen bonding of the diflunisal anion was studied, thereby revealing a new application of ion sensor potentiometry.